The impact of dermatological toxicities of anti‐cancer therapy on the dermatological quality of life of cancer patients. (13th February 2012) - Ra, H.S.; Shin, S.J.; Kim, J.H.; Lim, H.; Cho, B.C.; Roh, M.R.
Abstract Background One of the most common side effects of anti‐cancer therapies is treatment‐induced skin changes, referred to as dermatological toxicities. These dermatological toxicities are noteworthy since they have a negative association with quality of life (QoL). Objectives To evaluate the impact of dermatological toxicities on QoL of cancer patients and to identify the relationship between disease‐related characteristics and QoL and changes in skin protective behaviours following anti‐cancer therapy. Methods Cancer patients (n = 80: stage II–IV) in a longitudinal prospective study completed a battery of questionnaires at the time of enrolment and after 3 months of anti‐cancer therapy. QoL, skin toxicities, smoking and drinking behaviour, sun‐protective and skin care behaviour assessments were performed before and at 3 months after anti‐cancer therapy. QoL was measured with the Dermatology Life Quality Index (DLQI). Results A total of 73 patients completed the study. Among them, 48 patients (65.8%) experienced at least grade 1 skin toxicity at 3 months after anti‐cancer therapy. Hair loss, hyperpigmentation and dry skin were the most common dermatological toxicities. The mean baseline DLQI score changed from 1.38 to 3.49 at 3 months after anti‐cancer therapy. Domain 1 (symptoms and feelings, 1.38 points) was the most greatly impacted among patients by anti‐cancer treatment. Patients who experienced at least grade 1 skin toxicity (P = 0.001, 95% CI: 1.939–4.899), employed (P = 0.042, 95% CI: 0.030–1.476), more highly educated (P = 0.030, 95% CI: 0.161–3.132), and diagnosed with gastric cancer (P = 0.001, 95% CI: 2.141–8.250) or renal cell cancer (P = 0.002, 95% CI: 2.731–11.364) showed significantly higher DLQI scores. Patients showed significant change in skin protective behaviour such as use of body moisturizer (P = 0.021) and change in drinking behaviour (P = 0.006) at 3 months following anti‐cancer therapy. Conclusion Dermatological toxicities due to anti‐cancer therapy affect the QoL of cancer patients. Therefore, health care professionals should pay attention to the psychological effects of skin problems and educate cancer patients to adapt proactive skin protective behaviours to minimize dermatological toxicities of anti‐cancer therapy and maximize QoL.